IMPACT OF POLITICIAN’S LANGUAGE POLITENESS ON PUBLIC TRUST IN TALK SHOW - Kurniawan, Roni (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2024)
This study examines the impact of politeness strategies used by politicians on public trust. The data is sourced from the YouTube channel "Metro TV," specifically the episode "Tangan Besi Sri Mulyani," which features an interview between Andy F. Noya as the host and Sri Mulyani, the Minister of Finance of the Republic of Indonesia, as the guest. Methodologically, the study is divided into three stages: analyzing the politeness strategies used by both the host and the guest, identifying overall polite/impolite behaviors of the host and guest, and analyzing public sentiment through comments on the YouTube channel. The findings reveal that language politeness does not significantly impact public trust. However, in conflict situations, such as disputes between the host and guest, politeness can play a crucial role in restoring positive perceptions. Politeness is generally associated with good ethics and positive attitudes, while impoliteness is seen negatively and can trigger criticism of the impolite party and support for the polite one. Responding to impoliteness with politeness is considered good etiquette that can enhance support, and impoliteness is not always viewed negatively if understood as a defense against prior rudeness from the interlocutor. The conclusion of this study suggest that while politeness strategies in political interviews may not affect public trust, politeness still plays an important role in improving public perception during disputes or conflicts.